Global Mean Sea Level. Time Trends and Persistence with Long Range Dependent Data - Gil-Alana, Luis Alberiko (Frontiers in Physics, 2021)
Global mean sea level data are examined in this work by looking at the presence of time trends in the context of long memory or long range dependent processes. By looking at both seasonal signals retained and seasonal signals removed data from 1992 to 2020, the results show that the two series display significant time trend coefficients and high levels of persistence.